Housing valuation, wealth perception, and households' portfolio composition - Vale, S.; Camões, F. (EcoMod2017, 2017)
This paper empirically explores the relationship between wealth perception from homeownership and households’ preference towards asset categories pooled by risk. We use household survey data from the Household Finance and Consumption Survey to obtain a measure of the rate of housing valuation to be used in regressions against shares of safe, medium risk, and risky assets from a single portfolio. Shares are treated as a fraction of total wealth and estimated with fractional multinomial logit models and fractional logit models. Data shows incomplete household portfolios along with housing capturing the largest share of households’ wealth in accordance with the literature (e.g. Campbell, 2006). Our findings indicate robust empirical evidence that perceived wealth from the rate of housing valuation matters to portfolio choices. The estimations predict that an increase in the rate of housing valuation increases the demand for risky assets of mixed type, together with negative effects on the demand for safe deposits held within the strictly financial portfolio.